Functional Bakery Products: Technological, Chemical and Nutritional Modification - Piotr Zarzycki; Anna Wirkijowska; Urszula Pankiewicz (Applied Sciences)
Increasing consumer interest in the health benefits of various foods has driven the development of new food products and prompted modifications to the recipes and technologies used for the production of traditional items [...]